Evaluation of the humoral immune response to primary and booster covid-19 vaccination (Revista Contexto & Saúde, 2026)
This study aimed to evaluate the efficacy of the primary and booster vaccination response against COVID-19. This prospective cohort study was conducted in the Archipelago of Fernando de Noronha (Pernambuco, Brazil). A total of 350 adults (≥18 years), with and without previous SARS-CoV-2 infection, were included. Data collection occurred between May 2020 and May 2022. Serum levels of anti-SARS-CoV-2 IgG were evaluated before vaccination (T0), after the primary vaccination schedule with homologous vaccines (CoronaVac or ChAdOx1 – AstraZeneca/Oxford-Fiocruz), and after the heterologous booster dose with BNT162b2 (Pfizer-BioNTech). Detection of IgG antibodies was performed using a chemiluminescent immunoassay. Data were analyzed using GraphPad Prism 9.0 and SPSS 18.0 software, applying the Mann-Whitney and Sidak tests for longitudinal comparisons (p < 0.05). Participants were divided into two groups according to previous SARS-CoV-2 infection: infected (G1; n = 81) and not infected (G2; n = 269). In both groups, anti-SARS-CoV-2 IgG levels significantly increased after the primary vaccination scheme compared with pre-vaccination levels (p < 0.05). In G1, anti-SARS-CoV-2 IgG levels reduced after an interval between 14 and 30 days. After the booster dose with BNT162b2, anti-SARS-CoV-2 IgG levels increased and kept high for 233 days after vaccination. The decline in antibody levels observed after the primary vaccination with two homologous doses reinforces the need for a heterologous booster dose to maintain the humoral immune response.